PERAN ENDORSER TERHADAP BRAND ATTITUDE DAN PERILAKU PEMBELIAN ONLINE: STUDI KASUS UMKM DI KOTA RANTEPAO, TORAJA UTARA, SULAWESI SELATAN - Lisa Kurniasari Wibisono; Mince Batara (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Promotions carried out by an endorser through social media such as Instagramare not only used by large companies in their marketing activities, but can alsobe used to market products from local MSME brands to increase product salesonline. Based on the stimulus-organism-response (SOR) paradigm, this studywill examine the role of endorsers in brand marketing and online buyingbehavior in the context of MSMEs in the Rantepao City area, North Toraja,South Sulawesi. Based on the number of variables and indicators used in thisstudy, a representative sample approach was used in sampling, so the numberwas 80 to 160 respondents. Purposive sampling technique which is part of thenon-probability sampling technique will be used to determine the respondentswho are the sample. During the study, a set of questionnaires with 5 Likert scaleanswer choices will be given to the target respondents as the primary datasource. After the research data is obtained, the data will then be analyzed forvalidity and reliability tests. After the data is found to be valid and reliable, thepartial least squares (PLS) analysis method will be used to test the proposedhypothesis. Statistical analysis carried out includes: evaluation of the outer andinner models. The expected results and outputs in this study are to producereferences for MSME business actors in carrying out business activities that useendorsers as a way to strengthen brand attitudes when consumers make onlinepurchasing decisions. The results of this study are at TKT 2. The results obtainedfrom this research will be published in the Accredited National Journal: Journalof Business Economics, State University of Malang Accredited Sinta 4 with pISSN: 0853-7283 and e-ISSN: 2528-0503 as Mandatory Outcomes. accepted andSinta 3 Accredited Petra Christian University Marketing Management Journalwith p-ISSN: 1907235X and e-ISSN: 1907235X as additional outputs submitted.And the 2021 National Seminar on Management and Business Economics(SNMEB) as Additional Outcomes.